ILLOCUTIONARY SPEECH ACTS ANALYSIS IN TOM CRUISE’S INTERVIEW - Haucsa, Ghasella Makhpirokh; Marzuki, Abdul Gafur; Alek, Alek; Hidayat, Didin Nuruddin (Universitas Swadaya Gunung Jati, 2020)
This study is an analysis of illocutionary speech acts performed in Tom Cruise?s interview in promoting his movie. This study aims to describe the types as well as the functions of illocutionary speech acts performed by both the interviewer and the interviewee. Moreover, this study also describes the most and the least used illocutionary speech acts performed in the interview. This study uses qualitative method employing descriptive analysis design. The data source of this study is collected by downloading the video of the interview from YouTube. The data are observed and transcribed into written form. Furthermore, the data are categorized into some types of illocutionary speech acts. The result showed that there are four kinds of illocutionary speech acts which are performed in Tom Cruise?s interview which are representative, commissive, directive, and expressive. Here, the representative speech acts was categorized as the most performed speech in that interview. The result of the present study showed that Tom Cruise tended to convey his utterance to give statements of fact or to describe things that he believed to be true. Meanwhile, the percentage of the most performed or the most used speech acts to the least one in Tom Cruise?s interview is: representative (48.7%), expressive (38.5%), commissive (7.7%), directive (5.1%), and declarative (0%).